2018
DOI: 10.1186/s12893-018-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Relevant prognostic factors influencing outcome of patients after surgical resection of distal cholangiocarcinoma

Abstract: BackgroundDistal cholangiocarcinoma (DCC) is a rare but over the last decade increasing malignancy and is associated with poor prognosis. According to the present knowledge curative surgery is the only chance for long term survival. This study was performed to evaluate prognostic factors for the outcome of patients undergoing curative surgery for distal cholangiocarcinoma.Methods75 patients who underwent surgery between January 2000 and December 2014 for DCC in curative intention were analysed retrospectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
4
18
0
1
Order By: Relevance
“…Surgical resection by pancreaticoduodenectomy remains the only definitively curative therapy for the long-term survival of distal cholangiocarcinoma patients [ 4 ]. And the 5-year survival rate of distal cholangiocarcinoma after pancreatoduodenectomy ranged from 22 to 47% [ 5 7 ]. Lymph node metastasis is widely accepted as an important survival factor for distal cholangiocarcinoma patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection by pancreaticoduodenectomy remains the only definitively curative therapy for the long-term survival of distal cholangiocarcinoma patients [ 4 ]. And the 5-year survival rate of distal cholangiocarcinoma after pancreatoduodenectomy ranged from 22 to 47% [ 5 7 ]. Lymph node metastasis is widely accepted as an important survival factor for distal cholangiocarcinoma patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) is a primary liver cancer with features of differentiation of cholangiocytes, the epithelial cells lining the intra- and extrahepatic portions of the biliary tree [ 1 ]. An increasing incidence of CCA has been reported over the last few decades [ 2 ]. It is the second most frequent type of primary liver cancer and comprises malignancies with high inter- and intratumor heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative biliary drainage is recommended in patients with cholangitis, intense symptomatic jaundice, jaundice before neoadjuvant chemotherapy, delayed surgery, severe malnutrition, and liver or kidney failure, as well as in candidates for portal vein embolization[6,46]. Despite the fact that preoperative biliary drainage has been seen to reduce morbidity and mortality overall[3], there is some controversy over its indication in patients with severe jaundice: some studies have shown a greater risk of postoperative complications[47] and lower survival, possibly as a result of delaying surgery[48]. Nevertheless, a more recent retrospective study recommends preoperative biliary drainage in order to increase survival[49].…”
Section: Endoscopic and Radiological Managementmentioning
confidence: 99%